Learning Strategies and Styles of a Part Time Job Student With Good Achievement (A Case Study of a Successful Part Time Job EFL Learner) - Rigel Sampelolo; Haryanto Atmowardoyo (Universitas Negeri Makassar, 2016)
This research intended to find out the comprehensive description of learning strategies, and styles applied by the part-time job University student at the Christian University of Indonesia Toraja, and all the contributing factors that affect his learning process. The method used in this research was grounded theory. The instruments were an interview, direct observation, and documentation. The participant of the research was the part-time job student academic year 2014/2015 at English Department of Christian university of Indonesia Toraja. The result of the research showed that (i) the learning strategies performed by this student were the direct and indirect strategy. The direct strategy included memory, cognitive, compensation strategies while indirect strategy covered affective and social strategy. (ii) Learning styles perform by this student were visual and kinesthetic style. And (iii) the factors contributing to student's success were Personality, Motivation, English practicing, Social interaction, and Self-management. Keywords: learning strategies, learning styles, contributing factors to learning process, part time job student.